Pertanggungjawaban Orang Tua Terhadap Anak Pelaku Tindak Pidana Kecelakaan Lalu Lintas yang Menyebabkan Kematian (Studi Pada Satlantas Polres Pematangsiantar) - Panjaitan, Syaidilla; Syahbana, Tengku Erwin (LPPM Universitas Ekasakti Padang, 2024)
This research aims to analyze how parents are responsible for children who commit criminal acts. Children often do not receive the right parenting style by parents or institutions for child development and education, so many children are trapped in juvenile delinquency. Giving permission for minors to drive motorized vehicles is a form of lack of parental responsibility towards their children, because apart from requiring driving skills, a strong mentality and a sense of responsibility are needed when driving, this is necessary to prevent undesirable things from happening. like a traffic accident. However, if the child is the perpetrator of a traffic crime and the parents find out, they can be held criminally responsible for the traffic crime committed by their child. So it can be concluded that in this research the author describes the requirements for criminal responsibility of a child as a criminal as well as the role of responsibility of the child's parents in the responsibility of parents towards children who are perpetrators of criminal traffic accidents which cause death in Pematangsiantar.